2014
DOI: 10.1089/thy.2013.0133
|View full text |Cite
|
Sign up to set email alerts
|

Higher Incidence of Tall Cell Variant of Papillary Thyroid Carcinoma in Graves' Disease

Abstract: The incidence of PTC in GD-positive patients is higher than that in GD-negative patients. Aggressive variants of PTC, such as the TCV, were more frequent in nodular micro-PTC. These findings suggest that prompt and meticulous evaluation of nodules in any patient with GD associated with nodular alterations must be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
17
3
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 32 publications
4
17
3
5
Order By: Relevance
“…A more recent prospective study has shown that in patients with thyroid nodules elevated serum concentration of Tg Ab, but not serum thyroid peroxidase Ab, is an independent predictor for thyroid cancer [42]. Our findings are also in agreement with studies that showed that patients with Graves' disease are at a higher risk of thyroid carcinoma [43,44,45]. …”
Section: Discussionsupporting
confidence: 91%
“…A more recent prospective study has shown that in patients with thyroid nodules elevated serum concentration of Tg Ab, but not serum thyroid peroxidase Ab, is an independent predictor for thyroid cancer [42]. Our findings are also in agreement with studies that showed that patients with Graves' disease are at a higher risk of thyroid carcinoma [43,44,45]. …”
Section: Discussionsupporting
confidence: 91%
“…We explored the conventional (i.e., the miRNA−target relationships) and unconventional properties (i.e., the protein-coding ceRNA network and the indirect, modulatory contribution) of PTC miRNAs, providing valuable information about critical miRNAs and mRNAs from respective networks linking to the tumor biology. Consistent with our findings, a subset of Hashimoto's thyroiditis harbored some precursor lesions with molecular characteristics of PTC3839, suggesting frequent lymphocytic infiltration in this malignancy, and a higher incidence rate of TCPTC in patients with Graves' disease was also reported40. In this study, we demonstrated that TCPTC and, secondly, CPTC possess more immune activities under miRNA regulation than FPTC, indicating the involvement of immunological factors to different extents in PTC variants.…”
Section: Discussionsupporting
confidence: 89%
“…with AITD than in those without AITD and that they may be a 209 premalignant condition to PTC [20,21,22]. Our results, concerning 210 lymphoid cells, demonstrate unprecedently that these cells are 211 attacked by oxidative damage in PTC and AITD.…”
mentioning
confidence: 68%